Reconstructing the southern Greenland Ice Sheet and deep ocean circulation during the Plio-Pleistocene intensification of Northern Hemisphere glaciation - Blake-Mizen, K (University of Exeter, 2019)
The Greenland Ice Sheet (GrIS) is thought to have reached modern-like extents during cold stages for the first time during the Plio-Pleistocene intensification of Northern Hemisphere glaciation (iNHG, ~3.6–2.4 million years ago, Ma). However, questions remain regarding the spatial maturation of the southern GrIS during this time – a region thought to be particularly sensitive to changes in climate – including its extent during the mid-Piacenzian warm period (mPWP; 3.264–3.025 Ma), considered an analogue to near-future climate with atmospheric CO2 levels >400 ppmv and temperatures elevated by ~2–3 °C relative to today. Difficulties in obtaining long continuous sediment core records back to the late Pliocene in the subpolar North Atlantic, as well as chronological uncertainty in existing records, have previously hampered efforts to address these unknowns. In this thesis, I present high-resolution records of ice-rafted debris concentration and provenance, environmental magnetics and elemental X-ray fluorescence (XRF) spanning ~3.2–2.2 Ma from North Atlantic Integrated Ocean Drilling Program Site U1307 on Eirik Drift, just offshore southern Greenland. The study benefits from a newly-resolved high-fidelity relative paleointensity-based age model, the first of its kind for high-latitude sediments deposited during this interval, which enables variability in the records to be accurately and precisely dated. This multi-proxy approach enables constraints to be placed on the spatio-temporal evolution of iceberg-calving margins on southern Greenland, as well as contemporaneous changes in surface water productivity and delivery of glaciofluvial silt via the deep Western Boundary Undercurrent (WBUC) to Eirik Drift during iNHG. Provenance analysis of ice-rafted debris pinpoints the evolution of important modern-day southern Greenland iceberg-calving sources, revealing that a modern-like GrIS with extensive southern iceberg-calving margins had developed by ~2.4 Ma. Elevated glaciofluvial erosion throughout the mPWP traced by ...